The glory a novel - Wouk, Herman 1915-2019 (Little, Brown, 1994)
This sequel to The Hope continues the Jewish experience into the twentieth century including the Yom Kippur War, the Entebbe rescue, and the beginning of the peace process.
Keywords: Geschichte 1973-1993; Historical fiction.; Israel -- Fiction; Israel; Fiktionale Darstellung; Historical fiction